KAJIAN SEJARAH PERADABAN ISLAM: PENGARUH BANI ABBASIYAH TERHADAP PEMBELAJARAN DAN PENDIDIKAN - Hartoyo, Hartoyo; Habibi, Rohim (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
The golden period of science in the Islamic world was marked by the support of the Abbasid rulers, scholars with the establishment of Baitul Hikmah, This article discusses how the influence of the Abbasid golden period on learning and education, this research uses a descriptive qualitative approach with data obtained from library research. The results of this research are as follows: The influence of the Abbasid dynasty in Islamic education provides insight into the educational systems and practices that developed at that time. It is important to understand the foundations of modern education in the Islamic world and appreciate its rich intellectual heritage. In addition, the implementation of a structured curriculum in science teaching in schools contributes to the understanding of science by students. Learning the basic concepts of science helps students understand how science works, while schools play an important role in facilitating learning through interactive methods that are relevant to the needs of learners.